Pengaruh Kebijakan Direktur terhadap Kinerja Perusahaan dalam Novel Tuan Direktur Karya Hamka - Aulia Sita Uttami; Ayu Nabilah Aristawidya; Eva Dwi Kurniawan (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to see the influence of the director's policy on a company contained in a literary work. The literary work used in this research is entitled Tuan Direktur by Hamka. The problem identified in this study is how the character's policy affects the performance of his company and the importance of coworkers. The descriptive qualitative method is used to describe and analyze the policies and strategies taken by the character Tuan Direktur in leading his company. Stakeholder theory becomes the theoretical basis to understand how the director's policies can affect various parties involved or interested in the company. The analysis was conducted by considering the perspectives and interests of various stakeholders, including employees, shareholders, customers, and the surrounding community. The results show that the director's policies in the novel include factors that make the policies appropriate or inappropriate. Each policy has a different impact on company performance and affects the interests of stakeholders differently. The implication of this study is the importance of the director's role in forming policies that consider the interests and perspectives of various stakeholders. By understanding the implications of directors' policies, organizations can improve corporate strategy and management to achieve better and sustainable performance.